Ambient air quality and the risk for Chronic Obstructive Pulmonary Disease among Metro Manila Development Authority traffic enforcers in Metro Manila: An exploratory study. Issue 2 (1st June 2021) - Seposo, Xerxes; Arcilla, Audrey Lynn A.; De Guzman, Jose Guillermo N.; Dizon, Enrico Miguel S.; Figuracion, Andrea Nova R.; Morales, Christina Micaela M.; Tugonon, Pauleena Katriona A.; Apostol, Geminn Louis C.
Abstract: Background: Air pollution and poor ambient air quality are significantly related to multiple health risks. One associated disease is chronic obstructive pulmonary disease (COPD), a preventable disease with several contributing factors and one of the leading causes of morbidity/mortality locally and globally. A potentially high‐risk population are traffic enforcers who are constantly exposed to air pollution. In the Philippines, the MMDA has the widest coverage in traffic management. The study determined the risk of COPD among Metro Manila Development Authority (MMDA) traffic enforcers in relation to ambient air quality level, as well as identified other factors that increase the risk of developing COPD. Methods: Fifty‐two MMDA traffic enforcers deployed in PM2.5 air quality sensor areas in Metro Manila from 2016 to 2018 were recruited through stratified sampling. The International Primary Airways Guidelines (IPAG) questionnaire was utilized to measure risk of COPD. Respiratory health and working history were obtained through questionnaires. Department of environment and natural resources provided PM2.5 ambient air quality data which aided in the construction of the Exposure‐Month Index. Ordinal logistic regression was used to examine the association of PM2.5 together with the relevant factors and the risk of COPD. Results: We found statistically significant associations between PM2.5 and COPD among high risk category [odds risk (OR): 1.24, 95% confidence interval (CI): 1.07–1.44]. Age (Moderate, OR: 1.16, 95% CI: 0.98–1.38 and High, OR: 10.06, 95% CI: 4.02–25.17) and chest pain (Moderate, OR: 68.65, 95% CI: 1.71–2.75 × 10 3 ) were potential risk factors, whereas body mass index (BMI) (OR: 0.05, 95% CI: 0.01–0.53) exhibited protective effect. Conclusions: Exposure to PM2.5 was associated with an increased risk of COPD among high‐risk category MMDA traffic enforcers. Age and chest pain were potential risk factors to risk of COPD, whereas BMI exhibited a potential protective effect. Results of this study can be used for clinical management of high‐risk populations, such that of MMDA traffic enforcers. Graphical abstract: